The Threshold Effect of Inflation on Regional Economic Growth in Indonesia - Ramadhaniyati, Resti; Gunawan, Ashari; Susanti, Susan; Triansyah, Fadli Agus (Almana : Jurnal Manajemen dan Bisnis, 2023)
Recent studies state that the relationship between inflation and economic growth is not linear. When inflation exceeds a certain threshold, it will have a negative impact on economic growth. This study aims to investigate the linear and non-linear relationship between inflation and economic growth in Indonesia using provincial panel data. The linear relationship was tested using a panel regression fixed effect model, while a non-linear relationship was tested using a panel regression threshold fixed effect model. When a linear test is carried out, inflation in Indonesia does not affect economic growth. When conducting a non-linear test, inflation in Indonesia has a positive impact on economic growth only when the value is below 2.11 percent. Meanwhile, when inflation exceeded 2.11 percent, economic growth in Indonesia slowed down. Inflation control policies must still be carried out to reduce the negative effects of inflation because high and fluctuating inflation is not good for the economy.